An Interview with ChatGPT on Emergency Remote Teaching: A Comparative Analysis Based on Human-AI Collaboration - Tülübaş, Tijen; Demirkol, Murat; Ozdemir, Tuncay Yavuz; Polat, Hakan; Karakose, Turgut; Yirci, Ramazan (Universitepark, 2023)
Background/purpose - ChatGPT, a recent form of AI-based language model, have garnered interest among people from diverse backgrounds with its immersive capabilities. Using ChatGPT to support or generate scientific research has also created an ongoing debate over its advantages versus risks. The present study aimed to conduct an AI-enabled research process using ChatGPT so as to evaluate its potential to generate an accurate, clear, concise, and unbiased information as these are essential elements of rigorous scientific work. Materials/methods - To achieve this aim, we worked on emergency remote teaching (ERT), which garnered significant interest due to its wide-spread use during the COVID-19 pandemic, and created opposing views, particularly in comparison to online teaching. We conducted a simultaneous query on ChatGPT-3.5 and 4 on five basic themes: (1) the definition and emergence of ERT, (2) the appropriateness of ERT for different grade levels, (3) a comparison between ERT and online teaching, (4) the possible outcomes of ERT, (5) the future prospects and uses of ERT, and we performed a comparative evaluation of these responses with regard to accuracy, clarity, conciseness, and potential bias. We also used Cohen's kappa to assess inter-rater agreement in our analysis. Results - The results indicated that both versions were capable of generating accurate information without significant bias although the responses lacked depth and insight with being somewhat repetitive. As the level of judgment required by the query increased, the performance of ChatGPT-4 was much better; it provided clearer and more concise responses with a more synthesized and detailed categories of information on ERT. Conclusion - Based on our results, we state that the cooperation of human and artificial intelligence is still warranted to ensure an accurate and reliable output from AI-based scientific queries. If ChatGPT is a plane with innovative technologies, there still needs to be a pilot in the cockpit to make use of these technologies in the best way so as to fly the plane safely to its destination. © 2023 by the author(s).
Keywords: AI in education; Artificial intelligence; chatbot; ChatGPT; emergency remote teaching; generative AI; OpenAI